Novel utilization of strand‐specific reverse transcription polymerase chain reaction in perioperative clinical decision making for SARS‐CoV‐2 polymerase chain reaction positive patients. Issue 6 (5th April 2022) - Jette, Christine G.; Wang, Tammy; Wang, Ellen; Man, Janice Y.; Mireles, Samuel; Maass, Birgit; Mathew, Roshni; Pinsky, Benjamin A.; Claure, Rebecca E.; D'Souza, Genevieve
Abstract: In order to prevent in‐hospital transmission and potential complications related to SARS‐CoV‐2 in the perioperative patient, most healthcare institutions require preoperative testing for SARS‐CoV‐2 prior to proceeding with elective surgery. The Centers for Disease Control and Prevention (CDC) recommends a time and symptom‐based duration of isolation for the presumed infectious period. The guidance to avoid retesting of asymptomatic patients in the 90 days following a positive reverse transcription polymerase chain reaction (RT‐PCR) test is because of the possibility of detection of non‐infectious viral shedding. When to reschedule asymptomatic patients who test RT‐PCR positive for SARS‐CoV‐2 preoperatively is of considerable debate, both from the perspective of ensuring a patient's full preoperative fitness, as well as reducing the risk of viral transmission within the hospital. We describe the novel perioperative use of a strand‐specific assay to detect minus strand ribonucleic acid (RNA) in a clinical decision‐making algorithm to determine optimal timing of elective surgery after a patient tests RT‐PCR positive for SARS‐CoV‐2. This is the first description in the literature of an attempt to further stratify patients who repeatedly test positive for SARS‐CoV‐2 into infectious versus non‐infectious for perioperative planning.